2003
DOI: 10.1007/s00244-002-2102-6
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of the Toxicity of Perfluorooctane Sulfonate (PFOS) on Selenastrum capricornutum , Chlorella vulgaris , Lemna gibba , Daphnia magna , and Daphnia pulicaria

Abstract: Perfluorooctane sulfonate (PFOS) is an anthropogenic compound found in trace amounts in many environmental compartments far from areas of production. This, along with the highly persistent nature of PFOS, presents a concern for possible effects in aquatic ecosystems. The objective of this study was to determine the toxicity of PFOS in representative freshwater organisms. Toxicity testing using standard laboratory protocols was performed on the green algae Selenastrum capricornutum and Chlorella vulgaris, the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
68
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(77 citation statements)
references
References 24 publications
5
68
1
Order By: Relevance
“…19,30) The 21-d LC 50 and survival NOEC values of Daphnia magna exposed to PFOA in this study are greater than 100 mg/l and are similar to those reported by Colombo et al 11) In their recently published study, the EC 50 and survival NOEC of Daphnia magna were reported to be greater than 88.6 mg/l after 21 days exposure. Compared with published data on the chronic toxicity of PFOS, the 21-d survival NOEC of 5 mg/l found for Daphnia magna in this study is similar to the value of 5.3 mg/l for Daphnia magna in the study of Boudreau et al, 16) but the 21-d LC 50 of 9.1 mg/l found for Daphnia magna in this study is lower than the 21-d LC 50 of 42.9 mg/l for Daphnia magna reported in the same study. 16) In addition, MacDonald et al reported a 10-d survival LC 50 of 0.045 mg/l for the aquatic midge (Chironomous tentans).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…19,30) The 21-d LC 50 and survival NOEC values of Daphnia magna exposed to PFOA in this study are greater than 100 mg/l and are similar to those reported by Colombo et al 11) In their recently published study, the EC 50 and survival NOEC of Daphnia magna were reported to be greater than 88.6 mg/l after 21 days exposure. Compared with published data on the chronic toxicity of PFOS, the 21-d survival NOEC of 5 mg/l found for Daphnia magna in this study is similar to the value of 5.3 mg/l for Daphnia magna in the study of Boudreau et al, 16) but the 21-d LC 50 of 9.1 mg/l found for Daphnia magna in this study is lower than the 21-d LC 50 of 42.9 mg/l for Daphnia magna reported in the same study. 16) In addition, MacDonald et al reported a 10-d survival LC 50 of 0.045 mg/l for the aquatic midge (Chironomous tentans).…”
Section: Discussionsupporting
confidence: 89%
“…Compared with published data on the chronic toxicity of PFOS, the 21-d survival NOEC of 5 mg/l found for Daphnia magna in this study is similar to the value of 5.3 mg/l for Daphnia magna in the study of Boudreau et al, 16) but the 21-d LC 50 of 9.1 mg/l found for Daphnia magna in this study is lower than the 21-d LC 50 of 42.9 mg/l for Daphnia magna reported in the same study. 16) In addition, MacDonald et al reported a 10-d survival LC 50 of 0.045 mg/l for the aquatic midge (Chironomous tentans). 17) Although Daphnia magna is an important species for ecotoxicological study, it may not be a sensitive test species for PFOS or PFOA toxicity and some less common aquatic test species should be considered for chronic toxicity tests.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Among freshwater cladocerans, Daphnia magna is probably the most commonly used test organism in ecotoxicological studies. Some toxicity tests have been performed on cladocerans for perfluoro-octane sulfonic acid and perfluorooctanoic acid (PFOA) or their salts [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%